2022
DOI: 10.1186/s13046-021-02197-x
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA TINCR facilitates hepatocellular carcinoma progression and dampens chemosensitivity to oxaliplatin by regulating the miR-195-3p/ST6GAL1/NF-κB pathway

Abstract: Background Long non-coding RNAs (lncRNA) have an essential role in progression and chemoresistance of hepatocellular carcinoma (HCC). In-depth study of specific regulatory mechanisms is of great value in providing potential therapeutic targets. The present study aimed to explore the regulatory functions and mechanisms of lncRNA TINCR in HCC progression and oxaliplatin response. Methods The expression of TINCR in HCC tissues and cell lines was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Sharing the same miRNA response elements as their cognate genes, lncRNAs could serve as ceRNAs. For instance, a study revealed that TINCR acts as a sponge for miR-195-3p and promotes hepatocellular carcinoma progression [41] . According to bioinformatics analysis, TINCR possessed potential binding sites for miR-424-5p and miR-424-5p could target the 3'UTR of ATG5 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Sharing the same miRNA response elements as their cognate genes, lncRNAs could serve as ceRNAs. For instance, a study revealed that TINCR acts as a sponge for miR-195-3p and promotes hepatocellular carcinoma progression [41] . According to bioinformatics analysis, TINCR possessed potential binding sites for miR-424-5p and miR-424-5p could target the 3'UTR of ATG5 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Our data from CTRs-EVs supports the upregulation of some particular miRNAs with previously validated targets that modulate GABAergic synapses (eg. miR-19a-3p, miR-211, miR-1180-3p, miR-941) (Arcila et al, 2014;Bernreuther et al, 2006;Chen et al, 2022;Hu et al, 2012;Jovasevic and Radulovic, 2021;Li et al, 2009;Luo et al, 2016;Mei et al, 2022;O'Connor et al, 1992;Wang et al, 2021;Xiao et al, 2015;Xu et al, 2019;2018a;Zou et al, 2016) (Table 2). Interestingly, the cysteine string protein, encoded by the DNAJC5 gene, resides in presynaptic terminals, clathrin-coated vesicles and neuroendocrine secretory granules and is involved in neurotransmitter release and most importantly has been linked to Huntington's and Parkinson's diseases (Chandra et al, 2005;Miller et al, 2003;Ruiz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, microRNA and lncRNA also regulate sialylation in HCC. Long noncoding RNA TINCR acted as a competing endogenous (ceRNA) to sponge miR-195-3p, thereby protecting ST6GAL1 from miR-195-3p-induced repression; subsequently, elevated ST6GAL1 promoted HCC progression and chemoresistance [ 50 ]. In addition, miR-26a, miR-548l, and miR-34a have been reported to inhibit the expression of ST3GAL5, which encodes Lactosylceramide alpha-2,3-sialyltransferase, to suppress HCC cell proliferation and migration [ 51 ].…”
Section: Protein Glycosylation Alterations In Hccmentioning
confidence: 99%